Atomic Absorption Spectrometric Determination of Trace Amounts of Copper in Natural Waters and Standard Biological Samples after Separation and Preconcentration onto Amberlite XAD-2 Loaded with 2-(5-Bromo-2-Pyridylazo)-5-Diethylaminophenol - Ali Taher, Mohammad; Mostafavi, Ali; Rohani, Tahereh (Asian Journal of Chemistry, 2010)
A procedure for separation and preconcentration of trace amounts of copper has been proposed. It is based on the adsorption of copper (II) ions solution onto a column of amberlite XAD-2 resin loaded with 2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (5-Br-PADAP). Copper is quantitatively retained on the column in the pH range 6.5-9.5 at a flow rate of 2 mL/min. The copper complex dissolved out from the column with 5 mL of dimethylformamide (DMF) and copper was measured by atomic absorption spectrometry at 324.8 nm. In this case, 0.15 μg of copper can be concentrated in the column from 600 mL of aqueous sample, where its concentration i's as low as 0.25 ppb. Eight replicate determinations of 2.0 ppm of copper gave a mean absorbance of 0.210 in final DMF solution with a relative standard deviation of 1.7%. The sensitivity for 1 % absorption was 42 ppb. The interference of a large number of anions and cations has been studied and the optimized conditions developed were utilized for the trace determination of copper in natural waters and various standard samples.